Živković S. (editor): Restoration of teeth with extensive crown damage, Data Status, Beograd, 2023 - Ilić Jugoslav (Serbian Medical Society - Dental Section, Belgrade, 2024)
This text reviews a book in the field of restorative dentistry, published at the end of 2023. Its content and importance for undergraduate and postgraduate teaching, as well as the entire dental professional and scientific public, were analyzed.